The Role of Block Chain to Enhance the Egyptian Public Service Performance - Aly, Wael Omran; Aly, Zeinab El Sayed Mahmoud (The Arab Journal of Administration, 2025)
The ability of blockchain technology to record transactions on distributed ledgers offers new opportunities for governments to improve efficiency, transparency, prevent fraud, and establish trust to the public service performance. However, blockchain adoption and use in the context of e-Government is rather unexplored in academic literature. In this paper we systematically review relevant research to understand the current research topics, challenges and future directions regarding blockchain adoption for e-Government. The results show that the adoption of blockchain based applications in e-Government is still very limited and there is a lack of empirical evidence. The main challenges faced in blockchain adoption in developing countries as Egypt are predominantly presented as technological aspects such as security, scalability and flexibility. From an organizational point of view the issues of acceptability and the need of new governance models are presented as the main barriers to adoption. Moreover, the lack of law and regulatory support is identified as the main environmental barrier of adoption. Based on the challenges presented in the literature, we propose some reforming pillars to ease the adoption of blockchain to the public sector to enhance the public service performance in Egypt.